A Descriptive Review of Selected Nonviral Enteric Illnesses Reported in Children in Quebec between 1999 and 2006. Issue 2 (2010) - Kaboré, Henri; Michel, Pascal; Levallois, Patrick; Déry, Pierre; Payment, Pierre; Lebel, Germain
Abstract : OBJECTIVE: To review the epidemiology of selected nonviral enteric illnesses reported in children in Quebec between 1999 and 2006. METHODS: Incidence rates were calculated to describe age, sex, temporal and geographical characteristics of the selected nonviral enteric cases reported in children who were between zero and four years of age. Standard descriptive methods were used to analyze the temporal and geographical distributions of the incidence rates. RESULTS: A total of 5068 cases were reported. Of these, three pathogens accounted for the majority of the infections: Giardia (32.52%), Salmonella (30.98%) and Campylobacter (30.82%). Salmonella was most frequent in children younger than one year of age, whereas comparable incidence rates for the three pathogens were calculated for children between one and four years of age. For Giardia, the geographical distributions showed that the highest rates were in areas with more than 100, 000 inhabitants (except Montreal, Quebec); for Salmonella, the highest rates were in Montreal; and for Campylobacter, the highest rates were in areas with fewer than 10, 000 inhabitants. No detectable trends were seen over the study period for the three pathogens. Seasonal summer peaks were noted for Salmonella and Campylobacter, contrasting with late summer to early autumn peaks for Giardia . CONCLUSION: Findings suggest that Giardia, Salmonella and Campylobacter were the most common causes of nonviral enteric illnesses reported in children in Quebec. Giardia cases seemed to arise from different sources and transmission routes than the other two pathogens. Characteristics specific to Campylobacter infections in children, namely its predominance in areas with low population densities, and to Salmonella infections, namely predominance in the Greater Montreal area, should be further investigated to better guide prevention and control measures.